Kesan pelaburan modal insan, R&D dan ICT ke atas pertumbuhan ekonomi Indonesia - , Aiyub (2017)
Investment in human capital, research and development (R&D) and ICT are now receiving serious attention from the Indonesian government through significant budget allocation. Nonetheless, compared to other South East Asian countries, investment in these sectors is still low. To achieve Indonesia's Vision 2025 of becoming a developed country and to be the world's top 12 countries, investment in these sectors is seen to be important to ensure the continuous growth of the Indonesian economy in the long run. There are vast literatures focusing on the determinants of the economic growth of Indonesia but most are focused on identifying the direct relationship between the investment in human capital, R&D and ICT, and economic growth. Studies on the effect of interaction between human capital and R&D on economic growth are found to be limited. Therefore, this study was conducted to measure the impact of investment in human capital, R&D and ICT with special emphasis on the effect of interaction between human capital and R&D on economic growth. This study used quarterly data for the period 1968-2014 with Auto Regressive Distributed Lags (ARDL) dan Ordinary Least Square (OLS) methods. The study found that investment in education, health, R&D and ICT, and the interaction between health and R&D have positive significant impact on economic growth, both in the short and long run. The interaction between education and R&D, however, positively and significantly affects economic growth only in the short run but is not significant in the long run. In conclusion, the findings show that increased investment in human capital, R&D and ICT are very important for the continuous growth of the Indonesian economy. Thus, the development policy of Indonesia should be directed towards achieving a balance between investment in human capital and R&D especially in health and R&D.